2009
DOI: 10.1111/j.1755-5922.2009.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Responses to Aspirin and Clopidogrel: Insights Using Short Thrombelastography

Abstract: There is significant variability in both baseline clotting tendency and response to antiplatelet therapy. Responses are associated with outcome. We have investigated whether differences could explain the increased risk observed in women presenting with coronary artery disease. We have utilized short thrombelastography to assess (i) baseline clotting responses, (ii) response to aspirin and clopidogrel, and (iii) post-treatment platelet reactivity in 48 young volunteers, 22 older patients and 18 patients with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 23 publications
3
32
2
Order By: Relevance
“…Interestingly, the current results based on a Cox model indicated that female patients had a much higher risk of experiencing ischemic events than did male patients, and a previous study yielded a similar finding. Several studies have indicated that HPR is more prevalent in females than males because of a stronger platelet aggregation reaction to platelet agonist stimulation (13)(14)(15). This might be caused by a high of clotting at the baseline, the effects of female hormone, or a diminished reaction to clopidogrel in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the current results based on a Cox model indicated that female patients had a much higher risk of experiencing ischemic events than did male patients, and a previous study yielded a similar finding. Several studies have indicated that HPR is more prevalent in females than males because of a stronger platelet aggregation reaction to platelet agonist stimulation (13)(14)(15). This might be caused by a high of clotting at the baseline, the effects of female hormone, or a diminished reaction to clopidogrel in female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hobson and his colleagues demonstrated that there were both an elevated baseline clotting tendency and a reduced response to clopidogrel in young healthy females as compared to that in males. No such differences among males and females were observed in an older or postmenopausal female (Hobson et al, 2009). By contrast, males had a higher risk of developing CAD as compared with females, with the highest relative risk in young adults.…”
Section: Discussionmentioning
confidence: 64%
“…This result was consistent with previous reports; caffeine inhibited platelet aggregation by up-regulating adenosine A 2A receptor, [19] and chronic coffee drinking decreased platelet aggregation. [20] For the influence of sex, previous studies in Caucasians reported that baseline platelet aggregation in females was higher than that in males, [21][22][23] whereas in a study conducted in a healthy Korean population CTs were reported to be significantly longer in females. [17] Although one possible reason for this inconsistency would be a race difference (Caucasian versus Asian), more studies will be needed to better understand the influence of sex on CT.…”
Section: Discussionmentioning
confidence: 88%